Polyethylene composite container bag and processing technology thereof

By using composite starch of corn amylose and glutinous rice amylopectin and gelling during the processing of polyethylene composite bags, the problem of water regeneration of inner starch is solved, the mechanical properties and antibacterial ability of the product are improved, and a more economical and environmentally friendly production process is achieved.

CN119749015APending Publication Date: 2025-04-04HAINAN JIAXIN PACKING CO LTD

Patent Information

Application Number
CN202411964418.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-30
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

The inner starch of existing polyethylene composite container bags is prone to regenerate and precipitate water molecules after cooling, resulting in a decline in overall performance and possible microbial growth.

Method used

The composite starch of corn amylose and glutinous rice amylopectin is used, and gelatinized and partially gelled during the processing process. Combined with the synergistic plasticization of glycerol and sodium polyacrylate, a more stable plastic layer structure is formed.

Benefits of technology

It improves the strength, stability and antibacterial ability of the polyethylene plastic layer, reduces bacterial growth, enhances the product's impact resistance and tear resistance, and reduces raw material costs and waste in the production process.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005217994540000101
    Figure BDA0005217994540000101
Patent Text Reader

Abstract

The invention discloses a polyethylene composite container bag and a processing technology thereof, and relates to the technical field of resin plastic processing, and the polyethylene composite container bag sequentially comprises a plastic woven cloth layer, a bonding layer and a polyethylene plastic layer from outside to inside; the polyethylene plastic layer comprises an outer layer, a middle layer and an inner layer; the inner layer comprises the following components in parts by weight: 4-8 parts of linear low-density polyethylene, 25-45 parts of high-density polyethylene, 20-30 parts of composite starch, 5-10 parts of glycerol, 15-25 parts of talcum powder, 4-6 parts of sodium polyacrylate and a proper amount of water; the composite starch comprises corn amylose and sticky rice amylopectin. The strength and stability of the plastic layer can be enhanced, and the overall processing performance of the plastic layer is improved; the impact resistance and the tear resistance of the product are improved; the product is more durable, the amount of released water molecules is small, and the influence on the polyethylene plastic layer can be reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of resin plastic processing, in particular to a polyethylene composite container bag and a processing technology thereof. Background Art

[0002] Polyethylene composite film is a multi-layer structure formed by combining different materials with polyethylene film using bonding technology. This composite material is formed by combining two or more materials tightly together through one or more composite processes to form a composite material with specific functions. The "composite" in the industry actually refers to "lamination", that is, bonding films of different properties together through a specific method and then sealing them to achieve the purpose of protecting the internal items, making polyethylene composite film widely used in the preparation of container bags.

[0003] Chinese patent, application number CN202111672888.X, a polyethylene composite packaging bag and its processing technology, S1, ingredients: middle layer: low-density polyethylene, PBAT; inner layer: linear low-density polyethylene, high-density polyethylene, starch, glycerol, talcum powder, sodium polyacrylate and appropriate amount of water; S2, preparation of blown film body; S3, laminating composite inner layer: mixing and kneading inner layer raw materials in a mixer, cutting and feeding into the laminating machine, extrusion coating on the inner surface of the blown film body, spraying BPTCA-N alkaline solution while hot, and then cooling, rolling and corona treatment of the surface layer to obtain polyethylene composite packaging film; S4, winding, slitting, bag making. The invention adds an appropriate amount of poly (butylene adipate / terephthalate) to the middle layer raw material, and adds plasticized starch to the inner layer, reducing the demand for petroleum industrial products, meeting the market demand for biodegradable plastics, and promoting the sustainable development of the industry. At the same time, the obtained composite film has good mechanical properties and excellent antibacterial activity.

[0004] However, since gelatinized starch is straight-chain starch, it is easy to regenerate and quickly separate a large number of water molecules after cooling, which reduces the overall performance and may cause microbial growth. Summary of the invention

[0005] The embodiments of the present application solve the problem of starch regeneration and water separation in the inner polyethylene plastic layer in the prior art by providing a polyethylene composite container bag and a processing technology thereof, thereby achieving better antibacterial effect and reducing bacterial growth.

[0006] The embodiment of the present application provides a polyethylene composite container bag, which comprises, from outside to inside: a plastic woven cloth layer, an adhesive layer, and a polyethylene plastic layer;

[0007] The plastic woven fabric layer is composed of the following components in parts by weight: 100 parts of polypropylene, 20-30 parts of ethylene-propylene random copolymer, 0.7-1.2 parts of maleic anhydride grafted polypropylene, 0.3-0.5 parts of silicon dioxide, and 0.1-0.3 parts of antioxidant;

[0008] The adhesive layer is composed of the following components in parts by weight: 100 parts of polyethylene, 35-40 parts of ethylene-methacrylic acid copolymer;

[0009] The polyethylene plastic layer includes an outer layer, a middle layer and an inner layer;

[0010] The outer layer comprises the following components in parts by weight: 20-30 parts of low-density polyethylene, 70-75 parts of linear low-density polyethylene, 0.3-0.5 parts of antistatic agent SP, 0.2-0.5 parts of erucic acid amide, 0.5-1.5 parts of silicon dioxide particles, and 0-5 parts of masterbatch;

[0011] Among them, the density of low-density polyethylene is 0.920g / cm-0.925g / cm, and the density of linear low-density polyethylene is 0.915g / cm-0.920g / cm;

[0012] The middle layer comprises the following components in parts by weight: 70-80 parts of low-density polyethylene and 25-35 parts of polybutylene adipate / terephthalate;

[0013] Among them, the density of low-density polyethylene is 0.920g / cm-0.925g / cm;

[0014] The inner layer comprises the following components in parts by weight: 4-8 parts of linear low-density polyethylene, 25-45 parts of high-density polyethylene, 20-30 parts of composite starch, 5-10 parts of glycerol, 15-25 parts of talc, 4-6 parts of sodium polyacrylate and appropriate amount of water;

[0015] Among them, the density of high-density polyethylene is 0.955g / cm2-0.965g / cm2, and the density of linear low-density polyethylene is 0.915g / cm2-0.920g / cm2; the composite starch includes corn straight-chain starch and glutinous rice amylopectin.

[0016] Furthermore, the particle size of the silicon dioxide is 100-200 nm.

[0017] Furthermore, corn amylose accounts for 40-70% of the total mass of the composite starch.

[0018] Furthermore, the outer layer of the polyethylene plastic layer also contains composite starch, the weight proportion of which is 30-50 parts.

[0019] Furthermore, the composite starch of the outer layer is dissolved in a proper amount of water before blow molding, and then the temperature is raised to 80° C. to gelatinize the starch, and then cooled to gelatinize part of the starch.

[0020] Furthermore, before gelatinization, 3-5 parts by weight of silica gel particles are added to the composite starch, and the particle size of the silica gel particles is 0.5-1 μm;

[0021] Furthermore, silica particles are loaded in the silica gel particles, and the particle size of the silica particles is 100-200 nm; the specific steps are:

[0022] The silica gel particles and silicon dioxide particles are dried separately, and then added into a high-speed mixer at a weight ratio of 5:1, and mixed for 1-2 hours to make them evenly mixed;

[0023] The mixed materials are transported to a fluidized bed reactor through an air flow conveying system, so that the silicon dioxide particles are evenly loaded onto the surface of the silica gel particles. The loaded materials are collected from the fluidized bed reactor, sieved, and dried to obtain loaded silica gel particles.

[0024] Furthermore, the particle size of the silicon dioxide particles in the polyethylene outer layer is 1-2 microns.

[0025] The processing technology of the above-mentioned polyethylene composite container bag is specifically as follows:

[0026] S1. Ingredients according to the formula:

[0027] S2, preparing a blown film body: placing the outer layer raw material and the middle layer raw material in a co-extrusion blown film unit and melting them into melts respectively, the surface layer melt temperature is 200°C-220°C, and the middle layer melt temperature is 240°C-260°C, and then blowing, cooling, pulling and shaping to obtain a blown film body;

[0028] S3, coating composite inner layer: the inner layer raw materials are mixed and kneaded in a mixer at a mixing temperature of 120°C-150°C, and then the sheets are cut and sent to a laminating machine, and the composite starch is gelatinized by high temperature, and then the temperature is lowered to gelatinize the straight-chain starch therein, and then glycerol and sodium polyacrylate are added to make the gelatinized starch melt again at high temperature in the laminating machine to become plasticized starch, and the melt temperature is 160°C-180°C, and then extrusion coating is applied on the inner surface of the blown film body, and 15g / L BPTCA-N alkaline solution is sprayed while hot, and the spraying amount is 0.8g / m, and then the surface layer is cooled and rolled and corona treated to obtain a polyethylene composite packaging film;

[0029] S4, rolling, slitting and bag making.

[0030] Furthermore, the temperature of the cooling gelation is 30-40°C.

[0031] One or more technical solutions provided in the embodiments of the present application have at least the following technical effects or advantages:

[0032] First, amylopectin has good hydrophilicity and is easy to gelatinize, which improves the compatibility of starch with plastic components such as polyethylene during processing; amylose has high crystallinity and thermoplasticity, which can enhance the strength and stability of the plastic layer. Mixing the two can combine the advantages of both and improve the overall processing performance of the plastic layer; amylopectin increases the softness and toughness of the plastic layer, improves the impact resistance and tear resistance of the product; amylose increases the strength and rigidity of the plastic layer, making the product more durable; mixing the two can make the product performance more balanced and meet the needs of different application scenarios; at the same time, amylose releases water molecules after cooling, affecting the stability and antibacterial ability of the polyethylene plastic layer of the container bag, while the regeneration effect of amylopectin is slower and the amount of water molecules released is smaller, which can reduce its impact on the polyethylene plastic layer.

[0033] Secondly, after gelatinization and partial gelatinization, the molecular chain structure of the composite starch becomes more flexible, and can better penetrate and entangle with the polyethylene molecular chain, thereby improving the compatibility of the two, forming a more uniform and stable plastic layer structure, reducing stratification and peeling, and improving the overall stability of the product.

[0034] Third, silica particles are added to the polyethylene plastic layer as a filler to enhance the mechanical properties of the plastic layer, and the silica particles loaded on the surface of the silica particles can significantly improve the wear resistance and scratch resistance of the plastic layer due to their high hardness and high wear resistance; silica particles change the melt rheological properties of the polyethylene plastic layer, making the melt more stable and reducing fluctuations and instability during processing; silica particles can reduce the melt viscosity of the plastic layer, making the processing smoother and reducing energy consumption and production costs.

[0035] Fourthly, the addition of silica particles improves the thermal stability of the polyethylene outer layer. Particles with large particle size can more effectively block the transfer of heat and reduce the risk of thermal deformation or degradation of polyethylene due to high temperature. The amylose and amylopectin in the composite starch form stronger cross-linking effects with functional groups such as hydroxyl groups on the surface of silica particles, fixing starch molecules and improving the stability and durability of the composite material. DETAILED DESCRIPTION

[0036] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by technicians in the technical field to which the present invention belongs; the terms used in the specification of the present invention are only for the purpose of describing specific embodiments and are not intended to limit the present invention; the term "and / or" used herein includes any and all combinations of one or more related listed items.

[0037] Embodiment 1

[0038] The polyethylene composite container bag of the present application comprises, from outside to inside, a plastic woven cloth layer, an adhesive layer, and a polyethylene plastic layer;

[0039] The plastic woven fabric layer is composed of the following components in parts by weight: 100 parts of polypropylene, 20-30 parts of ethylene-propylene random copolymer, 0.7-1.2 parts of maleic anhydride grafted polypropylene, 0.3-0.5 parts of silicon dioxide, and 0.1-0.3 parts of antioxidant;

[0040] The adhesive layer is composed of the following components in parts by weight: 100 parts of polyethylene, 35-40 parts of ethylene-methacrylic acid copolymer;

[0041] The polyethylene plastic layer includes an outer layer, a middle layer and an inner layer;

[0042] The outer layer comprises the following components in parts by weight: 20-30 parts of low-density polyethylene, 70-75 parts of linear low-density polyethylene, 0.3-0.5 parts of antistatic agent SP, 0.2-0.5 parts of erucic acid amide, 0.5-1.5 parts of silicon dioxide particles, and 0-5 parts of masterbatch;

[0043] The density of low-density polyethylene is 0.920 g / cm2-0.925 g / cm2, the density of linear low-density polyethylene is 0.915 g / cm2-0.920 g / cm2, and the particle size of silicon dioxide is 100-200 nm.

[0044] The middle layer comprises the following components in parts by weight: 70-80 parts of low-density polyethylene and 25-35 parts of polybutylene adipate / terephthalate;

[0045] Among them, the density of low-density polyethylene is 0.920g / cm-0.925g / cm;

[0046] The inner layer comprises the following components in parts by weight: 4-8 parts of linear low-density polyethylene, 25-45 parts of high-density polyethylene, 20-30 parts of composite starch, 5-10 parts of glycerol, 15-25 parts of talc, 4-6 parts of sodium polyacrylate and appropriate amount of water;

[0047] The density of high-density polyethylene is 0.955 g / cm2-0.965 g / cm2, and the density of linear low-density polyethylene is 0.915 g / cm2-0.920 g / cm2; the composite starch includes corn amylose and glutinous rice amylopectin, wherein corn amylose accounts for 40-70% of the total composite starch;

[0048] The processing method of the above-mentioned polyethylene composite container bag is specifically as follows:

[0049] S1. Ingredients according to the formula:

[0050] S2, preparing a blown film body: placing the outer layer raw material and the middle layer raw material in a co-extrusion blown film unit and melting them into melts respectively, the surface layer melt temperature is 200°C-220°C, and the middle layer melt temperature is 240°C-260°C, and then blowing, cooling, pulling and shaping to obtain a blown film body;

[0051] S3, coating composite inner layer: the inner layer raw materials are mixed and kneaded in a mixer at a mixing temperature of 120°C-150°C, and then the sheets are cut and sent to a laminating machine, and the composite starch is gelatinized by high temperature, and then the temperature is lowered to 30-40°C to gelatinize the straight-chain starch therein, and then glycerol and sodium polyacrylate are added to make the gelatinized starch melt again at high temperature in the laminating machine to become plasticized starch, and the melt temperature is 160°C-180°C, and then extrusion-coated on the inner surface of the blown film body, and 15g / L BPTCA-N alkaline solution is sprayed while hot, and the spraying amount is 0.8g / m, and then the surface layer is cooled and rolled and corona treated to obtain a polyethylene composite packaging film;

[0052] S4, rolling, slitting and bag making.

[0053] The technical solutions in the above embodiments of the present application have at least the following technical effects or advantages:

[0054] Amylopectin has good hydrophilicity and is easy to gelatinize, which improves the compatibility of starch with plastic components such as polyethylene during processing; amylose has high crystallinity and thermoplasticity, which can enhance the strength and stability of the plastic layer. Mixing the two can combine the advantages of both and improve the overall processing performance of the plastic layer; amylopectin increases the softness and toughness of the plastic layer, improves the impact resistance and tear resistance of the product; amylose increases the strength and rigidity of the plastic layer, making the product more durable; mixing the two can make the product performance more balanced and meet the needs of different application scenarios; at the same time, amylose releases water molecules after cooling, affecting the stability and antibacterial ability of the polyethylene plastic layer of the container bag, while amylopectin has a slower regeneration effect and releases less water molecules, which can reduce its impact on the polyethylene plastic layer;

[0055] The gelatinized amylopectin molecular chain is looser and easy to penetrate and entangle with the polyethylene molecular chain, thereby improving the compatibility of the two, forming a uniform mixture during the processing, and improving the overall performance of the plastic layer; the gelatinized amylopectin acts as a plasticizer in the plastic layer, which can increase the softness and toughness of the plastic layer; improve the impact resistance and tear resistance of the product, and make the product more durable; the gelatinized amylopectin reduces the melt viscosity of the plastic layer, making the processing process smoother; at the same time, due to the improved compatibility of amylopectin with polyethylene, the defects and defective product rate in the processing process are reduced;

[0056] By optimizing the compatibility of starch and polyethylene and the softness, toughness and other properties of the plastic layer, the overall quality of the product is improved. By using a more economical and easy-to-process mixture of amylopectin and amylose as composite starch, the cost of raw materials is reduced. At the same time, due to the improved processing performance, waste and defective product rates in the production process are reduced, further reducing production costs. Due to the optimization of product performance and the reduction of costs, container bags can be used in a wider range of fields. For example, they can be used to package heavy goods, chemicals and other occasions that require high strength and weather resistance.

[0057] Embodiment 2

[0058] The above embodiment further increases its overall performance, improves the uniformity of internal materials, and improves toughness by using a mixture of amylopectin and amylose without affecting its biodegradability. In order to further improve its wear resistance, further improvements are made on the basis of embodiment one.

[0059] The outer layer of the polyethylene plastic layer also includes composite starch, which has a weight ratio of 30-50 parts. When preparing the blown film body, it is placed together with the surface layer raw materials in a co-extrusion blown film unit to melt into a melt;

[0060] The composite starch of the outer layer is dissolved in a proper amount of water before blow molding, and then heated to 80°C to gelatinize the starch, and then cooled to gelatinize part of the starch;

[0061] The technical solutions in the above embodiments of the present application have at least the following technical effects or advantages:

[0062] After gelatinization and partial gelatinization, the molecular chain structure of the composite starch becomes more flexible, and can better penetrate and entangle with the polyethylene molecular chain, thereby improving the compatibility of the two, forming a more uniform and stable plastic layer structure, reducing delamination and peeling, and improving the overall stability of the product;

[0063] Gelatinized starch acts as a plasticizer in the plastic layer, which can increase the softness and toughness of the plastic layer, improve the strength and hardness of the plastic layer, and make the container bag have better impact resistance, tear resistance and ductility, and is suitable for more diversified application scenarios; Gelatinized starch can also reduce the melt viscosity of the plastic layer, making the processing process smoother, reducing energy consumption and production costs. At the same time, due to the improved compatibility of starch with polyethylene, it also reduces defects and defective product rates in the processing process, and improves production efficiency;

[0064] Silicon dioxide has the characteristics of high strength and high hardness, and is a commonly used reinforcing filler. Hydrogen bonds or other interaction forces are formed between gelatinized starch and silicon dioxide, so that the two are closely combined to jointly enhance the mechanical properties of the plastic layer; improve the strength and hardness of the plastic layer while maintaining a certain degree of softness and toughness. Silicon dioxide has excellent wear resistance and weather resistance, and can protect the surface of the plastic layer from erosion by the external environment; the interaction between gelatinized starch and silicon dioxide forms a more dense and uniform protective layer, which further improves the wear resistance and weather resistance of the plastic layer, extends the service life of the product, and reduces maintenance costs;

[0065] The interaction between gelatinized starch and silica forms a more complex network structure or interpenetrating network structure, which improves the stability and mechanical properties of the plastic layer, and also helps to improve the air permeability and moisture permeability of the plastic layer. The addition of silica will increase the melt viscosity of the plastic layer, making the processing difficult; gelatinized starch can reduce the melt viscosity of the plastic layer and alleviate the processing difficulties caused by silica.

[0066] The composite starch has adhesiveness and film-forming properties, and interacts with components such as polypropylene and ethylene-propylene random copolymer in the plastic woven cloth layer, thereby enhancing the adhesion between layers, improving the integrity and stability of the entire composite material, and reducing the occurrence of delamination and peeling. It can also improve the adhesiveness of the outer layer of the polyethylene plastic layer, thereby enhancing the bonding effect with the adhesive layer, improving the interlayer bonding strength of the entire composite material, reducing the occurrence of delamination and peeling, and also changing the surface properties of the outer layer of the polyethylene plastic layer, increasing the surface roughness or forming a microporous structure, and improving the bonding effect between the adhesive layer and the outer layer.

[0067] Embodiment 3

[0068] In Example 2, by adding composite starch to the outer layer of the polyethylene plastic layer, not only the wear resistance and weather resistance of the outer layer of the polyethylene plastic layer are improved, but also the degree of bonding with the adhesive layer and the plastic woven cloth layer is improved. In order to further improve the toughness of the container bag, rubber particles are also added to the outer layer, which is a further improvement on the basis of Example 2.

[0069] Before gelatinization, the composite starch of the outer layer is further added with 3-5 parts by weight of silica particles, wherein the silica particles are loaded with silica particles, the particle size of the silica particles is 100-200nm, and the particle size of the silica particles is 0.5-1μm;

[0070] The specific steps are:

[0071] The silica gel particles and silicon dioxide particles are dried separately, and then added into a high-speed mixer at a weight ratio of 5:1, and mixed for 1-2 hours to make them uniform;

[0072] The mixed materials are transported to a fluidized bed reactor through an air flow conveying system, so that the silicon dioxide particles are evenly loaded onto the surface of the silica gel particles. The loaded materials are collected from the fluidized bed reactor, sieved, and dried to obtain loaded silica gel particles.

[0073] The technical solutions in the above embodiments of the present application have at least the following technical effects or advantages:

[0074] Silica particles are added to the polyethylene plastic layer as fillers to enhance the mechanical properties of the plastic layer, while the silica particles loaded on the surface of the silica particles can significantly improve the wear resistance and scratch resistance of the plastic layer due to their high hardness and high wear resistance; silica particles change the melt rheological properties of the polyethylene plastic layer, making the melt more stable and reducing fluctuations and instability during processing; silica particles can reduce the melt viscosity of the plastic layer, making the processing smoother and reducing energy consumption and production costs;

[0075] The silica particles on the surface of the silica particles interact with the polyethylene molecular chains through hydrogen bonds, which improves the compatibility of the silica particles with the polyethylene plastic layer; the amylose and amylopectin in the composite starch can also interact with the silica particles on the surface of the silica particles, further improving the compatibility of the starch with the plastic layer; the silica particles also have a water-absorbing effect, reducing the negative impact of the regenerated precipitated water;

[0076] The silica gel particles change the surface properties of the outer layer of the polyethylene plastic layer, increase the surface roughness or form a microporous structure, improve the bonding effect between the adhesive layer and the outer layer; and stabilize the distribution of the composite starch in the plastic layer, reducing the migration and agglomeration of starch;

[0077] In addition, gelatinized starch can wrap and disperse silica and silica particles, reducing direct contact and collision between particles, thereby reducing the possibility of agglomeration. The three-dimensional network structure of starch provides more attachment points and dispersion space for silica particles, achieving uniform distribution of particles;

[0078] The hydroxyl groups on the starch molecular chain can form hydrogen bonds with the hydroxyl groups on the surface of the silica particles, stabilizing the silica particles in the three-dimensional network structure of the starch.

[0079] The amylose and amylopectin in the composite starch have different structures and properties, and their combined effect can further improve the dispersion and stabilization effect on silica particles.

[0080] Embodiment 4

[0081] In Example 3, silica gel particles loaded with silica are added to improve the toughness of the polyethylene plastic layer. In order to increase the overall stability of the container bag, the particle size of the silica particles in the polyethylene outer layer is increased based on Example 3.

[0082] Increase the silica particle size in the polyethylene outer layer to 1-2 microns;

[0083] The technical solutions in the above embodiments of the present application have at least the following technical effects or advantages:

[0084] The addition of silica particles improves the thermal stability of the polyethylene outer layer. Large-diameter particles can more effectively block the transfer of heat and reduce the risk of thermal deformation or degradation of polyethylene due to high temperature. The amylose and amylopectin in the composite starch form stronger cross-linking with the hydroxyl and other functional groups on the surface of the silica particles, fixing the starch molecules and improving the stability and durability of the composite material.

[0085] Large-sized silica particles can provide better dispersion space for composite starch, and starch molecules are more likely to adhere to large-sized silica particles to form a more uniform dispersion system, thereby improving the overall performance of the composite material. When the silica particle size increases, the stability of the silica particles in the polyethylene outer layer will also be improved. Large-sized silica particles can provide a better support and dispersion environment for the silica particles, reducing the possibility of their agglomeration and sedimentation. Silica particles with increased particle size can improve the interface bonding with the silica particles, reduce defects and stress concentration at the interface, and improve the overall strength and toughness of the composite material.

[0086] The huge silica particles create huge gaps around the polyethylene outer layer, providing more penetration and diffusion channels for additives such as starch, affecting their distribution and stability, allowing gelatinized starch and gelatinized starch to extend through the gaps to the inner layer, middle layer and adhesive layer of the polyethylene plastic layer, which not only increases the integrity of the polyethylene plastic layer, but also synergistically increases the bonding ability of the adhesive layer.

[0087] The polyethylene plastic layers prepared in the above-mentioned embodiments 1 to 4 were respectively subjected to transverse tensile strength, transverse elongation at break and anti-adhesion tests. The test results are shown in Table 1.

[0088] There are three experimental components:

[0089] Experiment 1: The outer layer includes the following components in parts by weight: 20 parts of low-density polyethylene, 70 parts of linear low-density polyethylene, 0.3 parts of antistatic agent SP, 0.2 parts of erucic acid amide, and 0.5 parts of silicon dioxide particles;

[0090] The middle layer includes the following components in parts by weight: 70 parts of low-density polyethylene and 25 parts of polyadipic acid;

[0091] The inner layer comprises the following components in parts by weight: 4 parts of linear low-density polyethylene, 25 parts of high-density polyethylene, 20 parts of composite starch, 5 parts of glycerol, 15 parts of talc, 4 parts of sodium polyacrylate and appropriate amount of water;

[0092] Experiment 2: The outer layer includes the following components in parts by weight: 25 parts of low-density polyethylene, 72 parts of linear low-density polyethylene, 0.4 parts of antistatic agent SP, 0.3 parts of erucic acid amide, 1 part of silicon dioxide particles, and 2 parts of masterbatch;

[0093] The middle layer includes the following components in parts by weight: 75 parts of low-density polyethylene and 30 parts of butylene terephthalate;

[0094] The inner layer comprises the following components in parts by weight: 6 parts of linear low-density polyethylene, 35 parts of high-density polyethylene, 25 parts of composite starch, 7 parts of glycerol, 20 parts of talc, 5 parts of sodium polyacrylate and appropriate amount of water;

[0095] Experiment 3: The outer layer includes the following components in parts by weight: 30 parts of low-density polyethylene, 75 parts of linear low-density polyethylene, 0.5 parts of antistatic agent SP, 0.5 parts of erucic acid amide, 1.5 parts of silicon dioxide particles, and 5 parts of masterbatch;

[0096] The middle layer includes the following components in parts by weight: 80 parts of low-density polyethylene and 35 parts of butylene terephthalate;

[0097] The inner layer comprises the following components in parts by weight: 8 parts of linear low-density polyethylene, 40 parts of high-density polyethylene, 30 parts of composite starch, 9 parts of glycerol, 25 parts of talc, 6 parts of sodium polyacrylate and appropriate amount of water;

[0098] The tensile strength and elongation at break refer to GB / T13022-1991 "Test method for tensile properties of plastic films";

[0099] In the anti-blocking test, two film samples, each measuring 100 mm x 200 mm, are brought into close contact with their inner surfaces in contact with each other, and then a load of 1 kg is applied along an area of ​​80 mm x 80 mm at 60°C for 72 hours to compress them into contact. Thereafter, one end of each of them is clamped to the upper load sensor of a tensiometer, and a PTFE-coated brass rod is inserted between the uncompressed portions of the film samples, the brass rod itself being connected to a metal frame mounted on the lower fixture of the tensiometer. When the lower fixture of the tensiometer is lowered, the brass rod will separate the 80 mm x 80 mm compressed portions in the middle of the film sample from each other, and the average force applied to pull the brass rod downward is the force required to separate the two layers of film or the adhesion force of the film.

[0100]

[0101]

[0102] Table 1

[0103] The amount of corn amylose in the table refers to the percentage of corn amylose in the total weight of composite starch.

[0104] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. Polyethylene composite container bag, characterized in that: From outside to inside: plastic woven cloth layer, adhesive layer, polyethylene plastic layer; The plastic woven fabric layer is composed of the following components in parts by weight: 100 parts of polypropylene, 20-30 parts of ethylene-propylene random copolymer, 0.7-1.2 parts of maleic anhydride grafted polypropylene, 0.3-0.5 parts of silicon dioxide, and 0.1-0.3 parts of antioxidant; The adhesive layer is composed of the following components in parts by weight: 100 parts of polyethylene, 35-40 parts of ethylene-methacrylic acid copolymer; The polyethylene plastic layer includes an outer layer, a middle layer and an inner layer; The outer layer comprises the following components in parts by weight: 20-30 parts of low-density polyethylene, 70-75 parts of linear low-density polyethylene, 0.3-0.5 parts of antistatic agent SP, 0.2-0.5 parts of erucic acid amide, 0.5-1.5 parts of silicon dioxide particles, and 0-5 parts of masterbatch; Among them, the density of low-density polyethylene is 0.920g / cm-0.925g / cm, and the density of linear low-density polyethylene is 0.915g / cm-0.920g / cm; The middle layer comprises the following components in parts by weight: 70-80 parts of low-density polyethylene and 25-35 parts of polybutylene adipate / terephthalate; Among them, the density of low-density polyethylene is 0.920g / cm-0.925g / cm; The inner layer comprises the following components in parts by weight: 4-8 parts of linear low-density polyethylene, 25-45 parts of high-density polyethylene, 20-30 parts of composite starch, 5-10 parts of glycerol, 15-25 parts of talc, 4-6 parts of sodium polyacrylate and appropriate amount of water; Among them, the density of high-density polyethylene is 0.955g / cm2-0.965g / cm2, and the density of linear low-density polyethylene is 0.915g / cm2-0.920g / cm2; the composite starch includes corn straight-chain starch and glutinous rice amylopectin.

2. The polyethylene composite container bag according to claim 1, characterized in that: The particle size of silica is 100-200 nm.

3. The polyethylene composite container bag according to claim 1, characterized in that: Corn amylose accounts for 40-70% of the total mass of complex starch.

4. The polyethylene composite container bag according to claim 3, characterized in that: The outer layer of the polyethylene plastic layer also contains composite starch, the weight proportion of which is 30-50 parts.

5. The polyethylene composite container bag according to claim 4, characterized in that: The composite starch of the outer layer is first dissolved in a proper amount of water before blow molding, and then heated to 80°C to gelatinize the starch, and then cooled to gelatinize part of the starch.

6. The polyethylene composite container bag according to claim 5, characterized in that: Before gelatinization, 3-5 parts by weight of silica gel particles are added to the composite starch, and the particle size of the silica gel particles is 0.5-1 μm.

7. The polyethylene composite container bag according to claim 6, characterized in that: The silica gel particles are loaded with silica particles, and the particle size of the silica particles is 100-200nm; the specific steps are: The silica gel particles and silicon dioxide particles are dried separately, and then added into a high-speed mixer at a weight ratio of 5:1, and mixed for 1-2 hours to make them uniform; The mixed materials are transported to a fluidized bed reactor through an air flow conveying system, so that the silicon dioxide particles are evenly loaded onto the surface of the silica gel particles. The loaded materials are collected from the fluidized bed reactor, sieved, and dried to obtain loaded silica gel particles.

8. The polyethylene composite container bag according to claim 1, characterized in that: The silica particles in the polyethylene outer layer have a particle size of 1-2 microns.

9. The processing technology of the polyethylene composite container bag according to any one of claims 1 to 8, characterized in that: Specifically: S1. Ingredients according to the formula: S2, preparing a blown film body: placing the outer layer raw material and the middle layer raw material in a co-extrusion blown film unit and melting them into melts respectively, the surface layer melt temperature is 200°C-220°C, and the middle layer melt temperature is 240°C-260°C, and then blowing, cooling, pulling and shaping to obtain a blown film body; S3, coating composite inner layer: the inner layer raw materials are mixed and kneaded in a mixer at a mixing temperature of 120°C-150°C, and then the sheets are cut and sent to a laminating machine, and the composite starch is gelatinized by high temperature, and then the temperature is lowered to gelatinize the straight-chain starch therein, and then glycerol and sodium polyacrylate are added to make the gelatinized starch melt again at high temperature in the laminating machine to become plasticized starch, and the melt temperature is 160°C-180°C, and then extrusion coating is applied on the inner surface of the blown film body, and 15g / L BPTCA-N alkaline solution is sprayed while hot, and the spraying amount is 0.8g / m, and then the surface layer is cooled and rolled and corona treated to obtain a polyethylene composite packaging film; S4, rolling, slitting and bag making.

10. The processing technology of the polyethylene composite container bag according to claim 9, characterized in that: The temperature for cooling and gelation is 30-40°C.

Citation Information

Patent Citations

  • Container bag for buffer solution

    CN114229246A

  • Polyethylene composite packaging bag and processing technology thereof

    CN114311906A

  • Degradable starch-based plastic and preparation method thereof

    CN115304893A

  • Curable composition, cured product, and method for producing the same

    JP2010070586A

Cited By

  • Multi-layer polyethylene composite inner bag for container bag and processing technology

    CN121821909A

  • Multi-layer polyethylene composite inner bag for flexible intermediate bulk container and processing technology thereof

    CN121821909B